Beyond the signs: A Semiotic Analysis of Bullying in the Korean Drama “The Glory” - Dwi Nugraha, Rama; Fadillah, Dani (COMMICAST, 2025)
This study aims to determine the signs that underlie bullying in a Korean drama entitled “The Glory”. “The Glory” is a Korean drama that is quite popular in several countries, especially in Indonesia, this drama raises the issue of bullying committed by a group of students against a student named Moon Dong Eun, where bullying often occurs in the school environment. This research uses a qualitative approach method, using documentation techniques for data collection, and applying Ferdinand De Saussure's theory. In the drama “The Glory”, the drama itself functions as a signifier, with the signifier being all the scenes from episode 1 to 16 depicting acts of bullying, and the signifier being the school, which serves as the place where the bullying incident against Moon Dong-Eun occurred. The conclusion of this study is that “The Glory” functions as a signifier, with the signifier being all the scenes from episodes 1 to 16 that were researched and related to bullying, and the sign is the school where the bullying incident against Moon Dong-Eun occurred. The contribution of this research lies in its ability to provide a semiotic analysis of bullying representation in popular media, particularly in Korean dramas, which can help raise awareness of bullying issues in educational institutions. Additionally, this study can serve as a reference for further research on the impact of media portrayals of bullying on public perception and policy-making related to anti-bullying measures in schools.